(untitled) (World Science, 2021)
Objective: to increase the efficiency of the training process of athletes in military aviation pentathlon through the additional introduction of crossfit exercises and cognitive training. Material and methods of research: analysis of literature sources, questionnaires, testing, statistical analysis. The study involved 48 first-year cadets of the Ivan Kozhedub Kharkiv National University of the Air Force (men), aged 17-18, including 38 candidates for masters of sports and 10 masters of sports. The obtained results: a combination in a single algorithm of training first-year cadets - candidates for the national team with VAP exercises for the development of motor coordination skills, develop the maximum number of competencies (motor abilities). Using crossfit exercises with maximum agility, accuracy, balance, flexibility, mobility in the joints, jumping, accuracy, rhythm and plasticity allow cadets to develop maximum physical performance and endurance. Conclusions: Exercises for the development of cognitive abilities allow you to understand in more detail and then perform new exercises, to concentrate as much as possible on the ultimate goal of the exercises. Pilates largely avoids high impact, high power output, and heavy muscular and skeletal loading. Pilates largely avoids high impact, high power output, and heavy muscular and skeletal loading.